Micro-pharmacokinetics: quantifying local drug concentration at live cell membranes - Gherbi, Karolina; Briddon, Stephen J.; Charlton, Steven J. (Nature Publishing Group, 2018)
Fundamental equations for determining pharmacological parameters, such as the binding afnity of a ligand for its target receptor, assume a homogeneous distribution of ligand, with concentrations in the immediate vicinity of the receptor being the same as those in the bulk aqueous phase. It is, however, known that drugs are able to interact directly with the plasma membrane, potentially increasing local ligand concentrations around the receptor. We have previously reported an infuence of ligand-phospholipid interactions on ligand binding kinetics at the β2-adrenoceptor, which resulted in distinct “micro-pharmacokinetic” ligand profles. Here, we directly quantifed the local concentration of BODIPY630/650-PEG8-S-propranolol (BY-propranolol), a fuorescent derivative of the classical β-blocker propranolol, at various distances above membranes of single living cells using fuorescence correlation spectroscopy. We show for the frst time a signifcantly increased ligand concentration immediatel adjacent to the cell membrane compared to the bulk aqueous phase. We further show a clear role of both the cell membrane and the β2-adrenoceptor in determining high local BY-propranolol concentrations at the cell surface. These data suggest that the true binding afnity of BY-propranolol for the β2-adrenoceptor is likely far lower than previously reported and highlights the critical importance of understanding the “micro-pharmacokinetic” profles of ligands for membrane-associated proteins.